Evaluation of Internal Control and Diagnostic Control System in Sales at PT ABC - Evanggelia Anugerah Tri Putri; Evony Silvino Violita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to evaluate the effectiveness of internal control and the Diagnostic Control System (DCS) at PT ABC. This multinational personal care company experienced sales fraud in the form of channel stuffing during the fiscal year (FY) 2024. Using a case study approach and data triangulation through observation, secondary document analysis, and interviews with four key informants, this study analyzes weaknesses in internal control based on the COSO (2013) framework, Simons’ (2000) DCS, and the Fraud Triangle Theory. The findings indicate that all components of internal control were ineffective. The DCS was also misaligned with corporate strategy, as performance indicators focused primarily on sales volume and incentive schemes encouraged dysfunctional behavior. The combination of target pressure, weak controls, and cultural rationalization explains the occurrence of fraud in accordance with the Fraud Triangle Theory. This study concludes that the fraud at PT ABC resulted from weak internal controls that created opportunities for misconduct, as well as an ineffective DCS that created pressure and rationalized such behavior. The recommendations include strengthening the monitoring function by appointing a fully accountable local director rather than a nominal representative, redesigning KPIs and incentive schemes based on historical sell-out data to end consumers, and fostering an integrity-driven organizational culture to prevent recurring fraud.